2019
DOI: 10.1101/687186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic shifts in gene body methylation correlate with gene expression and reflect trait conservation

Abstract: A subset of genes in plant genomes are labeled with DNA methylation specifically at CG residues. These genes, known as gene-body methylated (gbM), have a number of associated characteristics. They tend to have longer sequences, to be enriched for intermediate expression levels, and to be associated with slower rates of molecular evolution. Most importantly, gbM

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…Conservation and phenomenological coherence suggest important functions 21 . Indeed, gbM is associated with (small) gene expression differences across plant species 26,27 , represses aberrant intragenic transcripts 28 , and appears to be under natural selection 26,29,30 . Moreover, loss of methyltransferase function causes developmental abnormalities in honeybees 31 , animals in which methylation is principally restricted to gene bodies 32 .…”
mentioning
confidence: 99%
“…Conservation and phenomenological coherence suggest important functions 21 . Indeed, gbM is associated with (small) gene expression differences across plant species 26,27 , represses aberrant intragenic transcripts 28 , and appears to be under natural selection 26,29,30 . Moreover, loss of methyltransferase function causes developmental abnormalities in honeybees 31 , animals in which methylation is principally restricted to gene bodies 32 .…”
mentioning
confidence: 99%
“…However, whether gene body methylation directly regulates levels of gene expression has been controversial 52,53 . Phylogenetic analyses of methylated and unmethylated plant species as well as analyses of within-species variation of gene body methylation in plants 52,53,54 Our results point to the middle blastoderm stage as the crucial point where Nv-Dnmt1a has its strongest effects on the embryonic transcriptome. Our data also show that the indirect effects of Nv-Dnmt1a pRNAi are mediated by both disruption of mRNA degradation, and misregulation of transcription from the zygotic genome.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies posited that gene body methylation has an important role in facilitating high, steady levels of gene expression 17,36 . However, whether gene body methylation directly regulates levels of gene expression has been controversial 54,55 . Phylogenetic analyses of methylated and unmethylated plant species as well as analyses of within-species variation of gene body methylation in plants 54,55,56 led to at most weak effects of gene body methylation on gene expression, although the evolutionary conservation of gene body methylation indicated associated functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Takuno et al (2016) 37 showed that only 6% of genes in rice have high levels (>90%) of CG methylation compared to 24% of genes in the much larger (2,300 Mb) genome of maize. The contrast is even stronger for high (>90%) CHG methylation -12% vs. 1% of maize and rice genes, respectively -reflecting the strong positive correlation between gene CHG methylation and genome size [37][38][39] .…”
Section: Introductionmentioning
confidence: 98%